1967
DOI: 10.1017/s0022172400045678
|View full text |Cite
|
Sign up to set email alerts
|

The progression of herpes simplex virus to the central nervous system of the mouse

Abstract: 1. The strain HFEM of herpes simplex virus is highly virulent for the 5-week-old mouse when inoculated intracerebrally; the LD50 and the ID50 both being close to the egg infectious unit. It is also virulent when given intraspinally.2. When inoculated peripherally it seldom causes nervous symptoms in the normal mouse but regularly does so if inoculated into skin which has previously been given a subcutaneous injection of 10% sodium chloride.3. After intradermal inoculation of pretreated mice with strain HFEM, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…After uptake and primary replication in the upper respiratory tract, ADV spreads towards the central nervous system (CNS) by means of one or more of the cranial nerves such as the olfactory and trigeminal nerves (McFerran & Dow, 1965;Sabo et al, 1969;Wittmann et al, 1980). It is generally accepted that the neuron plays an important role in neural invasion by herpesviruses such as ADV and herpes simplex virus type 1 (HSV-1) (Cook & Stevens, 1973;Field & Hill, 1974;Hill et al, 1972;Kristensson et al, 1971 ;McCracken et al, 1973;Wildy, 1967). The replication cycle of herpesviruses in neurons has been studied most frequently with HSV-1 in rat or human neuronal cell cultures (Lycke et al, 1984(Lycke et al, , 1988.…”
Section: Laboratory Of Veterinary Virology Faculty Of Veterinary Medmentioning
confidence: 99%
See 1 more Smart Citation
“…After uptake and primary replication in the upper respiratory tract, ADV spreads towards the central nervous system (CNS) by means of one or more of the cranial nerves such as the olfactory and trigeminal nerves (McFerran & Dow, 1965;Sabo et al, 1969;Wittmann et al, 1980). It is generally accepted that the neuron plays an important role in neural invasion by herpesviruses such as ADV and herpes simplex virus type 1 (HSV-1) (Cook & Stevens, 1973;Field & Hill, 1974;Hill et al, 1972;Kristensson et al, 1971 ;McCracken et al, 1973;Wildy, 1967). The replication cycle of herpesviruses in neurons has been studied most frequently with HSV-1 in rat or human neuronal cell cultures (Lycke et al, 1984(Lycke et al, , 1988.…”
Section: Laboratory Of Veterinary Virology Faculty Of Veterinary Medmentioning
confidence: 99%
“…Information regarding in vivo transport of herpesviruses has been derived by studying the kinetics of dissemination of infectious HSV-1 in spinal nerves and their corresponding spinal ganglia (Cook & Stevens, 1973;Hill et al, 1972;Klein & DeStefano, 1983;Kristensson et al, 1971;Wildy, 1967). The ganglion contains the neural cell bodies and the nerves their extensions.…”
Section: Laboratory Of Veterinary Virology Faculty Of Veterinary Medmentioning
confidence: 99%
“…Most controversial is the role of HSV-specific serum IgG in protection of the nervous system. Studies using corneal and footpad routes of challenge with HSV have indicated no decrease in latent infection in mice receiving immune serum (41,61). Using the genital route of challenge, Schneweis et al demonstrated a decrease in the number of acutely and latently infected DRG upon transfer of immune serum to naive recipients (51), an observation that was recently confirmed in HSV-immune, B-cell-deficient mice…”
mentioning
confidence: 97%
“…During the initial infection, HSV-I multiplies in the epithelium, invades local nerve endings, and travels by retrograde axonal transport (Johnson, 1964;Wildy, 1967) to neuronal cell bodies in regional sensory ganglia (Stevens and Cook, 1971;Hill et al, 1972). Although some sensory neurons permit productive infection to occur and are destroyed, most sensory neurons survive the infection and retain the virus in a latent state.…”
Section: Introductionmentioning
confidence: 99%